1988
DOI: 10.1016/0014-5793(88)80656-2
|View full text |Cite
|
Sign up to set email alerts
|

Pardaxin induces aggregation but not fusion of phosphatidylserine vesicles

Abstract: The effects on membranes of pardaxin, an amphipathic polypeptide, purified from the gland secretion of the Red Sea Moses sole flatfish Purdachirus marmoratus are dosedependent and range from formation of voltage-gated, cation-selective pores to lysis. We have now investigated the interactions of pardaxin with small unilamellar liposomes. Light scattering showed that pardaxin (10-7-10-9 M) mediated the aggregation of liposomes composed of phosphatidylserine but not of phosphatidylcholine. Aggregation of phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Numerous studies have addressed the interaction of pardaxin with lipid membranes (7-14,30-36), but have not been based on detailed kinetic studies-focusing instead on endpoint permeation (8)(9)(10)31,33). We extend these studies by a methodical investigation of how the rate of vesicle permeabilization (calcein release) is affected by solution pH and lipid headgroup charge.…”
Section: Calcein Release Patterns Are Dependent On Lipid Headgroup Chmentioning
confidence: 99%
“…Numerous studies have addressed the interaction of pardaxin with lipid membranes (7-14,30-36), but have not been based on detailed kinetic studies-focusing instead on endpoint permeation (8)(9)(10)31,33). We extend these studies by a methodical investigation of how the rate of vesicle permeabilization (calcein release) is affected by solution pH and lipid headgroup charge.…”
Section: Calcein Release Patterns Are Dependent On Lipid Headgroup Chmentioning
confidence: 99%
“…Pardaxin was synthesized and showed the same biological activity as the natural form [22]. With pore-forming ability on lipid membranes [23], pardaxin demonstrated various potential antibacterial, antiviral, and neurotoxic activities [2225]. Our previous study revealed that pardaxin induced apoptosis in human cervical adenocarcinoma HeLa cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with previous studies by CD spectroscopy, which reported that in H 2 O, pardaxin is mostly unstructured, although it adopts a helical conformation upon addition of increasing amounts of TFE (37,38,57,58). We chose DPC micelles for this work because of the affinity of pardaxins for membranes containing phosphatidylcholine (12,39). In DPC detergent micelles, Pa4 is soluble up ϳ1.0 mM.…”
Section: Structure Of Pardaxin In Micelles-pardaxinmentioning
confidence: 99%